Towards planetary governance?. Issue 2 (15th March 2019) - Gill, Stephen
ABSTRACT: This contribution reflects on some aspects of the nature, history and potential future of global governance and world order. It offers brief suggestions on ways, consistent with the health and well-being of people and the planet, to help rethink how the objects and priorities of governance should change – towards more democratic and socially just forms of planetary governance.